Adolescent escitalopram prevents the effects of maternal separation on depression- and anxiety-like behaviours and regulates the levels of inflammatory cytokines in adult male mice. Issue 62 (November 2017) - Wang, Qi; Dong, Xiaomei; Wang, Yan; Liu, Mengxi; Sun, Anji; Li, Nannan; lin, Yiwei; Geng, Zhongli; Jin, Ye; Li, Xiaobai
Highlights: Maternal separation (MS) increased levels of depression, anxiety in adult male offspring mice. Adolescent escitalopram can prevents the effects of MS on depression- and anxiety-like behaviours. The underlying mechanisms of escitalopram intervention involved in inflammatory factors. Abstract: There is little research on the effects of adolescent administration of antidepressants on behavioural function and inflammation in early-life stressed adult mice. Using maternal separation (MS), a paradigm of early adversity, we investigated the effects of adolescent (PND 33-54) escitalopram (ES; 10 mg/kg) exposure on depression- and anxiety-like behaviours and the levels of inflammatory cytokines (interleukin [IL]-1β, tumor necrosis factor [TNF]-α, and IL-10) in the ventral hippocampus (HPV), prefrontal cortex (PFC), and serum in adult (PND 61) male offspring mice. The results showed that MS has no effect on locomotor activity, but increased depression-like behaviours in the saccharin preference test and increased anxiety-like behaviours in the social preference and elevated plus maze tests. MS increased the levels of IL-1β in the HPV, PFC, and serum, while decreasing the level of IL-10 in the HPV. Furthermore, adolescent ES treatment inhibited these depression- and anxiety-like behaviours, decreased the levels of IL-1β, and increased the level of IL-10 in the HPV. The results also showed that there are no effects of chronic escitalopram administration on normal behaviour in control mice. Taken together, the current data provide experimental evidence that MS increases depression and anxiety levels in adult male offspring. Additionally, the findings support the idea that early pharmacological intervention with ES may be an effective treatment for reducing the behavioral abnormalities induced by early adversity and regulating the underlying inflammatory mechanisms involved.